PENGARUH MATERI, METODE DAN KOMPETENSI PENGAJAR DALAM PELATIHAN CUSTOMER SERVICE TERHADAP KINERJA SALES COUNTER DAN SALESMAN DI JARINGAN BISNIS SEPEDA MOTOR HONDA DI INDONESIA - Widianto, Yasminta Kris; Handoko, Yunus; Karnawati, Tin Agustina (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2023)
Employees who have good performance, are directly proportional to the company's performance. There are so many ways to to improve employee performance, but one of them is through training which is expected to increase the knowledge, abilities and behavior. PT Astra Honda Motor, as a manufacturer and distributor of Honda motorcycles, also seeks to improve the capabilities of sales counters and salesman through Customer Service training. Based on observations, there are differences in performance in serving consumers between sales counters and salesman who have received training, and those who have not. Based on the results of internal data, it was found that 12% of sales counters and salesman had substandard performance in serving consumers and had not received Customer Service training materials. The results of interviews with 10 branch heads of the Honda motorcycle network also agreed that Customer Service training is an important component in improving the skills, knowledge and attitudes of sales counters and salesman. Based on observations, data and interviews, this study aims to determine and analyze the effect of the materials, methods and competencies of the Customer Service training instructor on the performance of sales counters and salesman. As a result, the materials, methods and competencies of the Customer Service training instructor have a significant positive effect on performance, either partially or simultaneously